Angiogenic potential is reduced in skeletal muscle of aged women. (22nd September 2020) - Olsen, L. N.; Hoier, B.; Hansen, C. V.; Leinum, M.; Carter, H. H.; Jorgensen, T. S.; Bangsbo, J.; Hellsten, Y.
Abstract : Key points: The risk of cardiovascular disease and associated skeletal muscle microvascular rarefaction is enhanced in women after menopause, yet knowledge about the angiogenic potential in ageing women is generally sparse. Aged healthy and sedentary women were found to present a markedly impaired capacity for proliferation of skeletal muscle derived microvascular endothelial cells compared to young women. Vascular endothelial growth factor (VEGF) levels in skeletal muscle myocytes and release of VEGF from myocytes tended to be lower in aged compared to young women. The aged women did not show a detectable increase in skeletal muscle capillarization with 8 weeks of intense aerobic cycle training. Combined, the findings indicate that aged women have a reduced potential for capillary growth in skeletal muscle which, with ageing, may lead to age‐induced microvascular rarefaction. Abstract: Skeletal muscle angiogenic potential was examined in cell cultures derived from aged and young women, and the effect of 8 weeks of intense cycle training on muscle capillary growth was determined in the group of aged women. Basal muscle samples were obtained from healthy sedentary aged ( n = 12; 64 ± 4.2 years) and young women ( n = 5; 24 ± 3.2 years) for endothelial cell and skeletal muscle myocyte isolation and experiments. In addition, the aged women completed an 8‐week training intervention. Peak oxygen uptake and muscle samples for histology and protein determination were obtained before and after the training period. Before training, muscle microdialysate was collected from the aged women at rest and during exercise. In Part 1 of the experiments, growth‐supplement stimulated proliferation of endothelial cells was ∼75% lower in cells from aged compared to young women ( P < 0.001). There was a tendency for a lower vascular endothelial growth factor (VEGF) concentration in muscle conditioned media ( P = 0.0696) and for a lower VEGF content in the myocytes ( P = 0.0705) from aged compared to young women. Endothelial proliferation was found to be highly dependent on mitochondrial function. Acute exercise resulted in a modest (1.3‐fold; P = 0.0073) increase in muscle interstitial VEGF protein in the aged women. In Part 2, 8 weeks of intense training did not change muscle capillarization ( P ≥ 0.1502) in the aged women, but led to an increased amount of muscle VEGF ( P = 0.0339). In conclusion, aged women have impaired angiogenic potential, which is associated with a compromised response both at the skeletal muscle myocyte and microvascular endothelial cell level. Key points: The risk of cardiovascular disease and associated skeletal muscle microvascular rarefaction is enhanced in women after menopause, yet knowledge about the angiogenic potential in ageing women is generally sparse. Aged healthy and sedentary women were found to present a markedly impaired capacity for proliferation of skeletal muscle derived microvascular endothelial cells compared to young women. Vascular endothelial growth factor (VEGF) levels in skeletal muscle myocytes and release of VEGF from myocytes tended to be lower in aged compared to young women. The aged women did not show a detectable increase in skeletal muscle capillarization with 8 weeks of intense aerobic cycle training. Combined, the findings indicate that aged women have a reduced potential for capillary growth in skeletal muscle which, with ageing, may lead to age‐induced microvascular rarefaction.